Generation Z's Satisfaction with Online Purchases of Local Brand Coffee During the Covid-19 Pandemic in Greater Jakarta: The Impact of E-Service Quality and Food Quality - Nonot Yuliantoro; Jessie Febriani; Maureen Manuela; Vida Elissa; Juliana; Rosianna Sianipar (Jurnal Mantik, 2022)
For any coffee shop business to achieve client happiness, especially when selling online, e-service and food quality are crucial considerations. Customers who could previously order directly are now using an internet meal delivery service to order the desired food or drink due to the COVID-19 epidemic. The purpose of this study was to ascertain whether the quality of food and electronic services had an impact on Generation Z's happiness with local brand coffee purchases made online during the Covid-19 pandemic. A survey method is employed in this study. An online questionnaire will be used to gather the data. Data collection will take place in October 2020 during the Covid-19 epidemic, with the target audience being Generation Z clients in Jabodetabek with an age range of 18 to 25. using a convenience sampling strategy for data collection. The PLS-SEM will be used to test the data analysis. According to the study's findings, the quality of electronic services has a favorable impact on customer happiness, and the quality of the food has a substantial impact as well.